Prosedur Perpanjangan Sertifikat Keselamatan Konstruksi Kapal Melalui Sistem SIMKAPEL pada Kantor KSOP Kelas I Dumai oleh PT. Samudera Sarana Karunia Dumai - Jean Chandradja; Fadiyah Hani Sabila (Jurnal Publikasi Ilmu Manajemen, 2025)
The paper aims to explain the Procedure for Extending Ship Construction Safety Certificates through the SIMKAPEL system at the KSOP Class I Dumai Office by PT. Samudera Sarana Karunia Dumai. The methods used in this research are field research (Field Research) and methods through library research (Library Research). The ship safety certificate extension process has been going well, starting with the shipping company appointed by the ship owner to carry out the safety certificate extension at the Dumai Class I Port Authority and Harbor Master's Office. Firstly, the agent attaches the complete documents or requirements needed in the application for the extension of the Ship Safety Certificate and inputs the requirements for the extension of the ship construction safety certificate through the shipping SIMKAPEL, then the KSOP officer receives the completeness and checks the requirements for extending the construction certificate ship and after the requirements are met and completed, the Dumai Class I KSOP officer will carry out an inspection of the ship while the ship is anchored or docked in the area Dumai Class I Port. After inspection and testing of the ship's seaworthiness by the Harbor Master's Office and the Dumai Class I Port Authority and the ship can be confirmed to be seaworthy, the SHSK will issue a ship construction safety certificate by the Dumai Class I KSOP Office.